2022
DOI: 10.1186/s12905-022-01845-4
|View full text |Cite
|
Sign up to set email alerts
|

“Why don’t I look like her?” How adolescent girls view social media and its connection to body image

Abstract: Background Adolescent girls appear more vulnerable to experiencing mental health difficulties from social media use than boys. The presence of sexualized images online is thought to contribute, through increasing body dissatisfaction among adolescent girls. Sexual objectification through images may reinforce to adolescent girls that their value is based on their appearance. This study explored how sexualized images typically found on social media might influence adolescent girls’ mental health,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 91 publications
1
10
0
Order By: Relevance
“…A recent Australian study among girls aged 14-17 identified body image as a major concern, reporting negative appearance comparisons when viewing images on social media. 21 Another study showed a gender difference, where high social media activity at age 10 was associated with a decline in wellbeing for females, but not for males. 22 Time spent with family has decreased in both grades over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Australian study among girls aged 14-17 identified body image as a major concern, reporting negative appearance comparisons when viewing images on social media. 21 Another study showed a gender difference, where high social media activity at age 10 was associated with a decline in wellbeing for females, but not for males. 22 Time spent with family has decreased in both grades over time.…”
Section: Discussionmentioning
confidence: 99%
“…Among students aged 15/16 years, one in three girls reported feeling sad about their inabilities, and we can only speculate whether this is related to problematic social media use, which tends to lead to comparisons of yourself and your abilities at a vulnerable age. A recent Australian study among girls aged 14–17 identified body image as a major concern, reporting negative appearance comparisons when viewing images on social media 21 . Another study showed a gender difference, where high social media activity at age 10 was associated with a decline in well‐being for females, but not for males 22 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, given the important role of social media, schools, parents, and peers should have the potential to counteract all negative BI messages online, including on social media, as adolescents begin to use social media and many experience pubertal changes and become more aware of their bodies and appearance. It should also be recognized that appearance comparisons in popular culture, including social media, exacerbate adolescents’ appearance and BI, and that society has a role to play in helping to counteract these negative messages (Papageorgiou et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This can be particularly powerful in a society that often places unrealistic and damaging expectations on individuals' appearances. 43,44 It is important to note that traditional body painting can sometimes be less effective on models with darker skin tones but UV painting can overcome this barrier to make the activity more inclusive for diverse public audiences. 45 Anatomical body painting has the potential to serve as a powerful tool for wider social and political engagement, especially in the current climate where issues around sexual health, reproductive rights, and gender equality are being discussed and debated.…”
Section: Anatomical Body Paintingmentioning
confidence: 99%